The Effect of Comorbidity between Tinnitus and Dizziness on Perceived Handicap, Psychological Distress, and Quality of Life - Miura, Masatoshi; Goto, Fumiyuki; Inagaki, Yozo; Nomura, Yasuyuki; Oshima, Takeshi; Sugaya, Nagisa (Frontiers in Neurology, 2017)
Tinnitus and dizziness are common complaints encountered in the department of otolaryngology. We hypothesized that when patients complain of both tinnitus and dizziness, perceived handicap, impairment of quality of life, and emotional distress are more severe than the patient who complain of either tinnitus or dizziness. The subjects for this study were 736 patients who visited Hino Municipal Hospital between August 2010 and March 2012, complaining of tinnitus or dizziness. The subjects were divided into three groups depending upon their chief complaints — group B had patients with both tinnitus and dizziness (N=75), group T had patients with tinnitus (N=145), and group D had patients with dizziness (N=516). Assessments were performed using Tinnitus Handicap Inventory (THI) for groups B and T, Dizziness Handicap Inventory (DHI) for groups B and D, Medical Outcomes Study 8-items Short Form Health Survey (SF-8), and Hospital Anxiety and Depression Scale (HADS). The THI score of group B was higher than that of group T. The scores of PCS (physical component of SF8) of groups B and D were lower than that of group T. However, there were no significant difference in the DHI scores of groups B and D, and the HADS scores of the three groups. While the physical quality of life was found to vary depending on the presence of dizziness in patients with tinnitus, it was not found to vary depending on the presence of tinnitus in patients with dizziness. It is therefore important to consider the functional impact resulting from dizziness in patients with tinnitus.